Institutional guidelines on maternal care and investigations following antepartum stillbirth - a national survey - Dana A. Muin; Sabrina Neururer; Veronika Rotter; Hermann Leitner; Stephanie Leutgeb; Peter W. Husslein; Herbert Kiss; Petra Kohlberger (BMC, 2021)
Abstract Background Antepartum stillbirth, i.e., intrauterine fetal death (IUFD) above 24 weeks of gestation, occurs with a prevalence of 2.4-3.1 per 1000 live births in Central Europe. In order to ensure highest standards of treatment and identify causative and associated (risk) factors for fetal death, evidence-based guidelines on clinical practice in such events are recommended. Owing to a lack of a national guideline on maternal care and investigations following stillbirth, we, hereby, sought to assess the use of institutional guidelines and clinical practice after IUFD in Austrian maternity units. Methods A national survey with a paper-based 12-item questionnaire covering demographic variables, local facilities and practice, obstetrical care and routine post-mortem work-up following IUFD was performed among all Austrian secondary and tertiary referral hospitals with maternity units (n = 75) between January and July 2019. Statistical tests were conducted using Chi2 and Fisher's Exact test, respectively. Univariate logistic regression analyses were performed to calculate odds ratio (OR) with a 95% confidence interval (CI). Results 46 (61.3%) obstetrical departments [37 (80.4%) secondary; 9 (19.6%) tertiary referral hospitals] participated in this survey, of which 17 (37.0%) have implemented an institutional guideline. The three most common investigations always conducted following stillbirth are placental histology (20.9%), fetal autopsy (13.1%) and maternal antibody screen (11.5%). Availability of an institutional guideline was not significantly associated with type of hospital, on-site pathology department, or institutional annual live and stillbirth rates. Post-mortem consultations only in cases of abnormal investigations following stillbirth were associated with lower odds for presence of such guideline [OR 0.133 (95% CI 0.018-0.978); p = 0.047]. 26 (56.5%) departments consider a national guideline necessary. Conclusions Less than half of the surveyed maternity units have implemented an institutional guideline on maternal care and investigations following antepartum stillbirth, independent of annual live and stillbirth rate or type of referral centre.